The Relationship of Self-Efficacy with Cyberbystander Behaviour in Adolescents - Zelda Noelle Farrenta Pattinasarany; Enjang Wahyuningrum (Universitas PGRI Yogyakarta, 2026)
The pervasive use of social media has exacerbated the issue of cyberbullying, with bystanders (cyberbystanders) playing a critical role in its dynamics. This study examines the relationship between self-efficacy and cyberbystander behaviour among adolescents. A quantitative correlational design was employed, involving 256 active social media users aged 18 to 21 years. Data were collected using the Cyberbullying Bystander Scale and the Defender Self-Efficacy Scale. Spearman's correlation analysis revealed a significant positive relationship between self-efficacy and cyberbystander behaviour (r = 0.556, p < 0.001). Adolescents with higher self-efficacy were more likely to act as defenders of cybervictims, whereas those with lower self-efficacy tended to remain passive outsiders.Furthermore, self-efficacy accounted for 34.1% of the variance in defender behaviour and 15.1% of the variance in passive outsider behaviour. The findings underscore the pivotal role of self-efficacy in promoting proactive defender interventions among adolescents in cyberbullying contexts. Enhancing self-efficacy could be a key component in interventions aimed at encouraging positive bystander behaviour online. Keywords: self-efficacy, cyberbystander, cyberbullying, adolescent, defender behaviour